(untitled) (Journal of Forestry, 2025)
The Natura 2000 (N2000) ecological network, one of the most important tools for preventing further biodiversity loss in the European Union and the world’s largest coordinated network of protected areas, is affected by the spread of invasive alien vascular plant taxa (IAPs). The aim of this research was to gain first insights into (1) the presence of IAPs in the selected Croatian N2000 sites designated under the Habitats Directive, and determine (2) potentially the most vulnerable sites. IAPs were recorded in 233 out of 373 of the selected N2000 sites (62%), while 76 of the total 77 IAPs recorded at the time for entire Croatia (99%) were documented in at least one site. In all but one N2000 site in which they were recorded, the IAPs had potentially suitable habitats for the establishment and spread of their populations. Additionally, 92% of the IAPs had potentially suitable habitats in all N2000 sites where they were recorded. In 94% N2000 sites where IAPs were recorded and target habitats were present, at least one recorded IAP could potentially threaten the target habitat(s). Eight species were considered as the potentially most worrisome IAPs recorded in Croatian N2000 sites, while ten sites were identified as the potentially most vulnerable. Avenues for additional research were identified, which could contribute to the improvement of management strategies and the conservation of target species and habitats in Croatian Natura 2000 sites.